Formation of Student Character Regarding Disciplinary Aspects of School Regulations - Elvi Silvia; Nurfarida Deliani; Juliana Batubara (Indonesian Journal of Islamic Education, 2023)
This research aims to determine the formation of students' character regarding the disciplinary aspects of regulations related to school regulations. The research method in this article is qualitative research with a descriptive approach. The type of research used in this article is field research with a descriptive qualitative approach. The results of this research are that character formation through disciplined behavior is very important for students' futures. Because disciplined behavior has characteristics such as obedience, obedience, loyalty, regularity and orderliness, it is the most important thing to achieve national education goals. Implementing student character formation through disciplinary behavior by teachers aims to encourage students to achieve more, have good personalities and have dignity as individuals. This research examines the formation of student character through instilling aspects of student discipline regarding school regulations. From the results above it can be concluded that character formation through disciplined behavior is very important for students' future. Disciplinary behavior has characteristics such as obedience, obedience, loyalty, regularity and orderliness which are the most important things to achieve national education goals. Implementing student character formation through disciplinary aspects aims to encourage students to achieve more, have good personalities.